Pengaruh Kecerdasan Emosional dan Minat Belajar Terhadap Hasil Belajar Pada Mata Pelajaran Ipa di SMP Negeri 6 Cilegon Kelas VII - Annisa Nurul Wahidah; Sjaifuddin; Trian Pamungkas Alamsyah (PendIPA Journal of Science Education, 2026)
The researchers at SMP Negeri 6 Cilegon hope to investigate how EQ and passion in learning affect students' performance in scientific classes. This study employs a survey methodology and employs methods of data analysis such as regression and correlation, making it quantitative in character. The Slovin formula was used to determine the sample size, which consisted of 163 individuals selected by the Simple Random Sampling method. This study's population included all 273 seventh graders of SMP Negeri 6 Cilegon. The emotional intelligence and learning interest variables were assessed using questionnaires, whereas the science learning outcomes variables were determined using grades from the odd semester report cards. In order to analyze the data, multiple linear regression analysis was used. According to the results, there is a partial, positive, and significant relationship between emotional intelligence and science learning outcomes at SMP Negeri 6 Cilegon. This relationship is supported by a t-value of 4.282 and a significance level of (0.000 < 0.05). Similarly, learning interest also has a partial, positive, and significant effect on science learning outcomes at this school, with a t-value of 3.868 and a significance level of (0.000 < 0.05). These two independent variables make up 20.4% of the scientific learning outcomes, whereas the remaining proportion is impacted by additional factors that are beyond the purview of this study.